Influence of Supplements on the Quality Parameters of Pleurotus sajor-caju (Fr.) Singer - , N. A. Munshi, K. A. Bhat and Fahim Amin, P.A. Sheikh*, Shaheen Kauser, M.Y. Ghani (Journal of Phytology, 2010)
Various supplements viz., Artemisia, soybean, ‘baisen’(Cicer arietinum) rice bran, apple pomace, wheat bran, ‘moong dal’ (Vigna radiate), maize flour at different concentrations (0.5, 1.0 and 1.5%) to a single base material i.e, paddy straw were evaluated for their influence on total number of flushes, average number and weight of fruit bodies and diameter of stipe and pileus. Artemisia recorded lowest average number (51.4) and highest weight (16.33g) of a fruit body. Whereas the highest average number (68.8) and lowest average weight (12.88) was registered in apple pomace. The average maximum diameter of pileus (12.33cm) was observed in Artemisia and lowest in apple pomace (10.89cm). Similarly, average maximum diameter of stipe (0.98cm) was recorded on soybean and lowest in maize flour (0.71cm). Key words: Pleurotus sajor-caju, Quality parameters, Supplements <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">P.A. Sheikh et al. Influence of Supplements on the Quality Parameters of Pleurotus sajor-caju (Fr.) Singer. J Phytol 2/10 (2010) 60-65